(3eLehYI QSGFd eG Hjf edhc GdCfOdS SdGWjf GdeZQHs
(3ChdgG (B:s
(3GdeHjf , hUGQJ GdTeS ef HYO SahQgG hYehe fhQgG efbHI GdeMjG eYUHI GdLHjf s
(3BNQgG (B:s
(3Cfgi Edi ebGece Cf GdTjN eY chfg eSJMb (B" s
(3fSNI YJjbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJGQjNs